Biogeomorphically driven salt pan formation in Sarcocornia-dominated salt-marshes - Escapa, Carlos Mauricio (2015)
Salt-marshes are under increasing threat, particularly from sea-level rise and increased wave action associated with climate change. The development and stability of these valuable habitats largely depend on complex interactions between biotic and abiotic processes operating at different scales. Also, interactions between biotic and abiotic processes drive internal morphological change in salt-marshes. In this paper we used a biogeomorphological approach to assess the impact of biological activities and interactions on salt pan formation in Sarcocornia-dominated salt marshes. Salt pans represent a key physiographic feature of salt-marshes and recent studies hypothesized that biogeomorphic processes could be related to salt pan formation in SW Atlantic salt-marshes. The glasswort Sarcocornia perennis is one of the dominant plants in the salt-marshes of the Bahía Blanca Estuary (Argentina) where they form patches up to 8 m in diameter. These salt-marshes are also inhabited in great densities by the burrowing crab Neohelice (Chasmagnathus) granulata whose bioturbation rates are among the highest reported for salt-marshes worldwide. A set of biological interactions between N. granulata and S. perennis appears to be responsible for salt pan development in these areas which has not been described elsewhere. The main objective of this work was to determine the ecological interactions occurring between plants and crabs that lead to salt pan formation by using field-based sampling and manipulative experiments. Our results showed that S. perennis facilitated crab colonization of the salt-marsh by buffering otherwise stressful physical conditions (e.g., temperature, desiccation). Crabs preferred to construct burrows underneath plants and, once they reach high densities (up to 40 burrows m− 2), the sediment reworking caused plant die-off in the central area of patches. At this state, the patches lose elevation and become depressed due to the continuous bioturbation by crabs. Thus, salt pans are generated in this case by a set of biogeomorphic processes that include pure ecological interactions such as plant facilitation of crab settlement and also indirect negative effects of crabs on plant survival. Furthermore, crab bioturbation affects sediment structure due to concentration of burrowing activity under plant canopies promoting elevation loss and leading, after a few years, to salt pan formation in a previously vegetated substrate.